EIS QUE LIVRAREI DA PRISÃO O MEU POVO ISRAEL E JUDÁ : AS PALAVRAS DE SALVAÇÃO EM JR 30-31 COMO PROJETO DE RETRIBALIZAÇÃO - Peterlevitz, Luciano Robson (2014)
The purpose of this thesis is to provide an exegetical interpretation of the prophecy from Jeremiah 30-31 from a social perspective. Jeremiah 30-31 forms a literary unit in the book of Jeremiah, composed of subunits that can be designated as pericopae. A large part of the salvific expectations from this literary text needs to be attributed to the books literary origin and comes from the social articulations produced by Jeremiah at the end of the 7th century and the beginning of the 6th century B.C., in support of the poor of the ancient Palestine society, Israel/North and Judah/South. The first salvific statements appearing in Jeremiah 30-31 occurred during the era of Josiah (Jer 30,10-11.18-21; 31,2-5). Salvific expectations originated during this period aimed at the Israelite population of the North. Another intense occurrence of the salvific expectation happened during the years immediately after the fall of Judah in 587 B.C., when Jeremiah again directed a word of hope to the poor of Israel/North, and also included in his message those who remained in the land of Judah/South after the Babylonian destruction. The following pericopae can be found in this scenario: 30,3.5-7.12-17; 31,15.16-20.21-22.27-28.31-34. This present thesis assumes that, in general, Jeremiah 30-31 is a reconfirmation of the demilitarization and breakdown of the urbanization of Jerusalem that happened during that period, being that this new political and economic scenario favored the under privileged people of Palestine. Tribalism is the model of the salvific expectations of the original Jeremiah literature. In the development of a new society, with renewed tribalism, free from the yoke of the monarchy and the imperialists, Jeremiah 30-31 defends the ownership of the lands by the rural people who suffered from the plunder under the Assyrian Empire and the kings of Judah. With the fall of the state of Judah, the poor could resume their lives and possess the land as a means of production and livelihood. The relationship between the words of salvation and tribalism can also be noted in other texts from the book of Jeremiah. The structural verbal proponent of destruction and reconstruction in 31,28 can be found in Jer 1,10; 18,7.9; 24,6; 42,10 e 45,4. The promises of salvation contained in Jer 1,10, 31,27-28 e 42,10 announce the continuity of life in the land of Judah after the catastrophe of 587 B.C. This idea can also be seen in Jer 23,5-6, 30,8-9. In Jer 24,6, on the other hand, we read about a promise for the exiles of Judah that lived in Babylonia under the tribal system. In Jer 3,6-13.19-25; 4,1-2, Jeremiahs salvific expectations present the path for a social reorganization through the conversion to Yahweh.